2014
DOI: 10.1002/jsfa.6753
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion ofPalmaria palmata(red seaweed) in Atlantic salmon diets: effects on the quality, shelf-life parameters and sensory properties of fresh and cooked salmon fillets

Abstract: Dietary P. palmata was ineffective at providing red coloration in salmon fillets, but pigment deposition enhanced fillets with a yellow/orange colour. Carotenoids from P. palmata may prove to be a natural pigment alternative to canthaxanthin in salmon feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…This was also reflected in the use of P. palmata as a supplement in salmon diets, but the level of influence was less profound when contrasted to the dietary inclusion of U. rigida (Moroney et al . ). While these studies found the fish pigmentation did not meet market standards, both feeding trials performed were void of commercial astaxanthin sources, often synthetic.…”
Section: Macroalgae In Fish Dietsmentioning
confidence: 97%
“…This was also reflected in the use of P. palmata as a supplement in salmon diets, but the level of influence was less profound when contrasted to the dietary inclusion of U. rigida (Moroney et al . ). While these studies found the fish pigmentation did not meet market standards, both feeding trials performed were void of commercial astaxanthin sources, often synthetic.…”
Section: Macroalgae In Fish Dietsmentioning
confidence: 97%
“…It was concluded that P. palmata can be a suitable component in feed for Atlantic salmon. Studies of the effects on the quality of fresh and cooked fish fillets when P. palmata was included in diets for Atlantic salmon showed the yellow/orange color was enhanced through deposition of algal pigments, and dietary inclusion of 50 g kg −1 of P. palmata may improve overall acceptability without negatively impacting texture, odor, or oxidation flavor …”
Section: Effects On Growth Performance Protein Utilization and Carcamentioning
confidence: 99%
“…Studies of the effects on the quality of fresh and cooked fish fillets when P. palmata was included in diets for Atlantic salmon showed the yellow/orange color was enhanced through deposition of algal pigments, and dietary inclusion of 50 g kg −1 of P. palmata may improve overall acceptability without negatively impacting texture, odor, or oxidation flavor. 91 Red macroalgae of the genus Porphyra, e.g. P. purpurea, P. yezoensis, and P. dioca, have been studied as protein sources in diets for different fish species.…”
Section: Red Macroalgaementioning
confidence: 99%
“…Palmaria and Porphyra spp. have been successfully trialled in mariculturing of salmon [54], sea urchins [55] and trout [16] and a partial substitution of fish meal with seaweed proteins was generally well received by fish. Different responses from seaweed feeding trials indicate that not all aquatic species can assimilate high protein plant-based diets or accumulate dietary pigments successfully [16,55].…”
Section: Protein Contentmentioning
confidence: 99%